An Analysis towards a Sustainable Energy System in Albania Highly Supported by Large Scale Integration of Wind Resources: A Case Study of Mamaj Wind Farm - Bebi, Elena; Malka, Lorenc; Konomi, Ilirian; Alcani, Majlinda (International Journal of Energy Economics and Policy, 2020)
This article presents a highly important and detailed techno-economic analysis of a grid-connected wind farm, considered as one of the most potential location in the south of Albania, part of Tepelena region, Mamaj village. The procedure of selection of the wind turbine type is performed by evaluating the maximum Capacity Factor (CF) among 15 different types of wind turbines applied using WAsP energy tool enabling the optimization of energy system while economic analysis uses a Monte Carlo simulation well designed on RETScreen Expert tool. This modeling framework can address some beneficial values and solution which can be used from policy makers in the country to better assess the penetration of renewable energy sources into a large scale by finding the exact selling price of electricity and correcting the latest decrease of bonus factor from 1.3 in 2019 to 1.2 in 2020, which should be adjusted by a factor of 1.4. To check the economic feasibility of this project, the parameter of net present value (NPV), internal rate of return (IRR) and simple payback period (SPB) are adjusted accordingly and the financial feasible investment zone is determined. Keywords: RES, Wind Power, Net Present Value, Internal Rate of return, Discount Rate (r), Simple Payback Period, WAsP, RETScreen Expert JEL Classifications: Q4, Q42, Q48 DOI: https://doi.org/10.32479/ijeep.10622